Seleksi Penerimaan Satpam dengan Menggunakan Metode Topsis - Rivaldi Fairuzza Hakfani (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
Selection System Candidate Security is aprogram created to assist the selection process of securitycandidates. In the selection of candidates for securityguards, there is a phenomenon in which potential securityguards who do not meet the criteria can qualify. In thisstudy built decision-based support system that can assistdecision makers in solving problems that exist in theSelection Prospective System Selection Satpam based onexisting criteria. This research uses TOPSIS method(Technique for Order Preference by Similarity to IdealSolution). TOPSIS is a concept where the best alternativenot only has the shortest distance from the ideal idealsolution, but has the longest distance from the ideal idealsolution. TOPSIS has many advantages including simpleand easy to understand, efficient computing and has theability to measure the relative performance of decisionalternatives in simple mathematical form. TOPSIS method iswidely used to solve the problem of decision making. Theresults of the research show that TOPSIS method can beused to help provide recommendations to select candidatesfor security guards and systems that are made to solveproblems in the ranking of prospective security guards.